TINJAUAN YURIDIS TERHADAP PERLINDUNGAN KONSUMEN PT. GOJEK INDONESIA CABANG SAMARINDA BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 - Lukman Hakim (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT This legal writing is a legal research using empirical research methods - Noematif data collection is done through field studies or premier data and secondary data that is in the form of interviews and literature study, analyzing the data used in the form of normative methods kualiatif against data sources that the data expressed in verbal with a theoretical qualification and starting point on the search effort of the principles and or information of this research was conducted on April 10, 2017 until 14 April 2017 in PT.GOJEK INDONESIA, jln Wahid Hasyim 02 No.28 RT 31 purpose from writing this thesis is to obtain concrete data related to the issues discussed both consumer protection for users of services Gojek as an online transport and courier services to be safe and comfortable, the results of the research shows that the PT.Gojek Indonesia provides insurance for consumers who use services as a Gojek tool terrace online portal and courier service in the event of an accident and also if there is damage and loss of consumer goods, consumers who feel aggrieved by the Gojek party to obtain consumer protection may claim compensation in accordance with the agreement of both parties and / or complain the matter to the Consumer Protection Agency Kalimantan East or Court.